Evaluation of phosphate sorption capacity and external phosphorus requirement of some agricultural soils of the southwestern Ethiopian highlands - Berhanu Dinssa; Eyasu Elias (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2021)
One of the most soil fertility management problems for crop production on acidic soils of the Ethiopian highlands is phosphorus fixation. The research was executed to assess the P-sorption capacity and to determine the external P requirement of different acidic soils in the Southwestern highlands of Ethiopia. Phosphorus sorption capacity (Kf) and its relation with selected soil characteristics were assessed for some major agricultural soils in the Ethiopian highlands to answer the questions, ‘What are the amount of P-sorption capacity and external P requirement of Nitisols, Luvisols, Alisols, and Andosols in Ethiopia?’. Twelve surface soil samples (at depth of 0-30 cm) were gathered and the P-sorption capacity was estimated. Phosphorus-sorption data were obtained by equilibrating 1 g of the 12 soil samples with 25 ml of KH2PO4 in 0.01 M CaCl2, having 0, 30, 60, 90, 120, 150, 180, 210, 240, 270, 300, and 330 mg P L-1 for 24 hours. The data were adjusted to the Freundlich adsorption model and the relationship among P-sorption and soil characteristics was established by correlation analysis.  Clay content and exchangeable acidity, organic matter, Al2O3, and Fe2O3 oxides have affected phosphorus-sorption at a significance level of (P < 0.05).  Alisols had the highest Kf value (413 mg kg-1) but Nitisols had the lowest Kf (280 mg kg-1). The external phosphorus fertilizer requirement of the soils was in the order of 25, 30, 32, and 26 mg P kg-1 for Nitisols, Luvisols, Alisols, and Andosols sequentially. The Kf varies among different soil types of the study area. The magnitude of the soil’s Kf was affected by the pH of the soil, soil OM content, and oxides of Fe and Al. Therefore, knowledge of the soils’ P retention capacity is highly crucial to determine the correct rate of P fertilizer for crop production.